An examination of nursing students' performance in and Satisfaction with a Patient Safety E-Learning Module. - Levett-Jones, Tracy; Bogossian, Fiona; Cooper, Simon; Hopmans, Ruben; McKenna, Lisa; Nguyen, Huy; Pich, Jacqui; Seaton, Philippa (Collegian, 2024)
The knowledge nursing students acquire during their undergraduate degree influences the quality of patient care they provide for many years to come. However, previous studies indicate that students may have a limited understanding of core patient safety concepts. The objectives of this study were to (i) examine nursing students' performance in an interactive patient safety e-learning module titled ' One shift, four patients ... a day in the life of a new graduate nurse' ; and (ii) explore students' level of satisfaction with the module using the Satisfaction with the Patient Safety E-Learning Module scale. A cross-sectional design was used with students' knowledge and levels of satisfaction examined using descriptive statistics. In total, 1038 third-year undergraduate nursing students from 22 Australian universities attempted the module. The mean correct score was 74%, but there were significant differences in knowledge levels evident across the four activities that comprised the module. Participants achieved the highest mean score in Activity 2 (Predicting, monitoring, and responding to adverse events [79%]) and the lowest in Activity 3 (Clinical reasoning [66%]). The mean score for Activity 1 (Infection control and medication safety) was 74%, and for Activity 4 (Cultural competence), the score was 77%. The level of student satisfaction with the module was high with responses to each survey item exceeding 4.0 out of 5.0. The Cronbach's alpha for the satisfaction scale was 0.99, and the Content Validity Index was >0.9. Universities are responsible for preparing nursing students to become safe clinicians. The results from this study indicate that participants' overall level of knowledge of key patient safety concepts was adequate. However, as knowledge is the foundation for safe practice, these results suggest that further attention to imbedding patient safety in nursing curricula is required.